International Incidents: The Law That Counts in World Politics - W. MICHAEL REISMAN, ANDREW R. WILLARD (Princeton University Press, 2014)
In November 1983, a notice was posted on the Yale Law School bulletin board announcing a new seminar to be offered in the spring semester. The seminar was called "The Incident as a Decision Unit in International Law." Since the words in the title were not exactly terms of art in the trivium and quadrivium, the notice set out, at rather unusual length, what was intended: An incident is an international dispute that shapes or reinforces elite expectations about lawfulness, in which the appraisal of lawfulness by relevant international actors occurs in a nonformal setting. The Soviet destruction of KAL 007, the U.S. invasion of Grenada and the Israeli attack on the Iraqi reactor are examples of recent incidents. Because of the structure of the international political system, most international decision is found in incidents rather than cases and judgments. Yet paradoxically, there is no accepted method for recording incidents. The discipline of international law has adopted the notion of the national judgment as its basic if not exclusive epistemic unit; statements of courts are expanded by generative logic into a codex which is taken to be international law. As a result, much international jurisprudence is not congruent with contemporary elite expectations that are reflected in practice. It serves neither descriptive nor predictive functions, contributing little to the performance of indispensable legal tasks. This seminar will attempt to develop a concise method for recording and appraising incidents in the hope that it can install a new genre in international law. It will use the research techniques of contemporary historiography and political science in addition to the methods of international law. Each student, alone or in collaboration with another, will be responsible for researching a particular incident. Each will circulate a draft to the other seminar participants and explain and defend it in a session. It is planned that the better papers in the seminar will be collected in a volume and published.